Preliminary Measurements of Airborne Particulate Matter and Carbon Dioxide Concentration Gradients in Three Indoor Environments Using Two Distinct Sampling Systems - Alfred Micallef (Sci)
Preliminary monitoring campaigns in three (nonindustrial) indoor environments (a corridor, a coffee room with a kitchenette, and a single-occupancy office, all located in the same public building) were carried out, in which the vertical concentration profiles of airborne particulate matter (inhalable, thoracic, and alveolic fractions, as well as PM10 and PM2.5) and carbon dioxide were determined using two distinct, purpose-built sequential sampling systems. One of the systems was specifically built for use with gas monitors and is based on the organ-pipe sequential air sampling technique. The second system better suited the sequential air sampling of particulate matter. Both systems were electronically controlled. Six receptor levels at heights of 0.25, 0.95, 1.25, 1.65, 2.15, and 2.75 m above the ground/floor were considered. The outcomes of the campaigns are presented. The larger-size particle fractions exhibited the most vertical variation in concentration. With respect to measurements at a height of 1.25 m above the floor, percentage differences as high as 80% were recorded. Given the appreciable measured variation in concentration over a height of approximately three meters, further investigation is warranted, especially in view of the exposure of humans of different heights, e.g., adults and children, and possibly different circumstances, e.g., standing and sitting.